Dielectric constant-based optimization for sustainable extraction of centellosides from Centella asiatica using bio-based solvents - Pakaweerachat, Pattarabhorn; Chysirichote, Teerin (My University, 2026)
This study systematically examined the influence of solvent polarity and extraction temperature on the recovery of four major centellosides: madecassoside (MAD), asiaticoside (ASI), madecassic acid (MDA), and asiatic acid (ASA) from Centella asiatica. Extractions were performed using ethanol-water, acetone-water, ethanol-ethyl acetate, and hexane-ethyl acetate mixtures at 30–70 °C, covering dielectric constants (ε = 2–70) that correspond to the polarity range of the selected solvent systems. Extraction yields (mg g⁻¹) are expressed on a dry-weight basis. Ethanol–water mixtures demonstrated the highest efficiency for polar glycosides, yielding 19.6 ± 0.3 mg g⁻¹ dry matter (mg g⁻¹ DM) for MAD and 17.2 ± 0.3 mg g⁻¹ DM for ASI at 70 °C, with temperature effects mainly attributed to enhanced mass transfer and no significant thermal degradation observed. In contrast, aglycones (MDA and ASA) achieved optimal yields (3.3–6.5 mg g⁻¹) in solvents with lower dielectric constants, where solvent composition predominated over temperature effects. Solvent polarity, expressed in terms of dielectric constant, provided a quantitative indicator linking solvent selection to centelloside recovery and solvent-temperature interactions. Ethanol-water systems are recommended for food and nutraceutical applications, while ethyl acetate-ethanol mixtures are suited for cosmetic formulations. This work establishes a polarity-temperature framework for enhancing extraction using bio-based solvents, contributing to more sustainable production of bioactive-rich extracts from C. asiatica for use in food, cosmetic, and pharmaceutical industries.
Keywords: Asiatic acid; Asiaticoside; Green extraction; Madecassic acid; Madecassoside; Solvent polarity